Small RNA sequencing reveals a comprehensive miRNA signature of BRCA1-associated high-grade serous ovarian cancer. Issue 11 (5th April 2016) - Brouwer, Jan; Kluiver, Joost; de Almeida, Rodrigo C; Modderman, Rutger; Terpstra, Miente Martijn; Kok, Klaas; Withoff, Sebo; Hollema, Harry; Reitsma, Welmoed; de Bock, Geertruida H; Mourits, Marian J E; van den Berg, Anke
Abstract : Aims: BRCA1 mutation carriers are at increased risk of developing high-grade serous ovarian cancer (HGSOC), a malignancy that originates from fallopian tube epithelium. We aimed to identify differentially expressed known and novel miRNAs in BRCA1 -associated HGSOC. Methods: Small RNA sequencing was performed on eight normal tubal and five HGSOC samples of BRCA1 carriers. Differential expression of a subset of known and novel miRNAs was validated by qRT-PCR on the samples used for small RNA sequencing and a second sample cohort comprising normal and HGSOC tissue of matched BRCA1 and non- BRCA carriers. Data from The Cancer Genome Atlas were used to determine the clinical relevance of the validated differentially expressed miRNAs. Results: 59 known and 20 novel miRNAs showed a significant >fourfold expression difference between normal tubal tissue and HGSOC. qRT-PCR validation confirmed a significant difference in expression levels for 10 out of 11 known miRNAs . Upregulation of two novel miRNAs could not be confirmed. Interestingly, for seven miRNAs a significant increase in expression was observed when comparing normal tubal tissue of postmenopausal women with premenopausal women. Expression levels of miR-145-5p significantly increased with International Federation of Gynecology and Obstetrics stage, while the expression levels of the other nine validated miRNAs were not associated with clinical characteristics. Conclusions: We report a comprehensive expression signature including both known and novel miRNAs of BRCA1 -associated HGSOC. Comparison with previous profiling studies showed a good overlap and a large number of miRNAs not reported to be differentially expressed in HGSOC before underscoring the importance of this study.